2019
DOI: 10.1002/ctpp.201900037
|View full text |Cite
|
Sign up to set email alerts
|

Flow control with plasma‐based actuator in different velocity regimes: Momentum and heat transfer effects

Abstract: In this study, control of the airflow by the direct current (DC) electrical discharge with bare electrodes has been investigated in different velocity regimes. The discharge characteristics of the plasma model are obtained numerically. An induced electrohydrodynamic (EHD) force on neutral flow was characterized based on momentum transfer from charged particles. The change in the incident flow parameters was studied by applying Navier-Stokes (N-S) equations, considering source terms arising from a weakly ionize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…The Electro-Hydro-Dynamic (EHD) body force is due to the momentum transfer from the charged particles to the neutral ones through collisions. As described in details in 56 , 57 , the true EHD body force is comprised of linear and nonlinear terms. The linear terms include the conduction terms of the current densities, the diffusion, and the charged particle generation 56 , 58 .…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Electro-Hydro-Dynamic (EHD) body force is due to the momentum transfer from the charged particles to the neutral ones through collisions. As described in details in 56 , 57 , the true EHD body force is comprised of linear and nonlinear terms. The linear terms include the conduction terms of the current densities, the diffusion, and the charged particle generation 56 , 58 .…”
Section: Governing Equationsmentioning
confidence: 99%
“…As described in details in 56 , 57 , the true EHD body force is comprised of linear and nonlinear terms. The linear terms include the conduction terms of the current densities, the diffusion, and the charged particle generation 56 , 58 . The non-linear term which is recently discussed by Mahdavi and Sohbatzadeh 57 , depends on the gradient of the electric field intensity and the variation of the plasma dielectric permittivity.…”
Section: Governing Equationsmentioning
confidence: 99%
“…It was also shown that the direction of the nonlinear body force in both positive and negative corona discharges is always from the wire to the cylinder. To consider the influence of linear (Coulomb force) and nonlinear body force in wire-cylinder configuration, the results of references [34][35][36] were used for both coronas. It was demonstrated that during the running of both coronas the electric current can be decomposed into DC and AC signals that characterize the corona process and distinguish positive and negative coronas.…”
Section: Introductionmentioning
confidence: 99%